Respuesta :

2x^3+x^2-2x+8 / x+2=

2x^2-3x+4

2x3+x2−2x+8 / x + 2=

6x+8 over x+2



Answer:

Quotient = [tex]2x^2 - 3x +4[/tex]

Remainder = 0

Step-by-step explanation:

Here, the given expression,

[tex]{2x^3 + x^2 - 2x + 8}\div {x + 2}[/tex]

By the long division, ( shown below )

We get,

[tex]\frac{2x^3 + x^2 - 2x + 8}{x + 2}=(2x^2 - 3x + 4)\times (x+2) +0[/tex]

Since,

Dividend = Quotient × Divisor + Remainder

Hence,

Quotient = [tex]2x^2 - 3x +4[/tex]

Remainder = 0

Ver imagen slicergiza